Banana Stem (Musa balbisiana Colla) as Potential Biosorbent to Remove Methylene Blue Dye in Wastewater: Isotherm, Kinetic, Thermodynamic Studies and Its Application: Banana stem biosorbent for removal methylene blue dye - Zein, Rahmiana; Akmal, Clalitya; Safni, Safni; Fauzia, Syiffa; Ramadhani, Putri (Applied Environmental Research, 2023)
Textile industries discharge various waste including dye waste to the environment. Dye waste such as methylene blue taints both aquatic and land ecosystem. Thus, the recent study employs banana stem (Musa balbisiana Colla), as an economical and environmentally friendly biosorbent for methylene blue removal. The chemically activated banana stem indicates the significant methylene blue uptake at pH 5, initial concentration of 800 mg L-1, contact time of 60 min, temperature at 25 °C with adsorption capacity of 71.5470 mg g-1. The adsorption process follows the Langmuir isotherm model (R2 = 0.9965) and pseudo order model which involve monolayer and chemical adsorption. The thermodynamic evaluation shows that the adsorption process occurs spontaneously and exothermic. The regeneration process indicates that the banana stem can remove methylene blue up to 90% after five times adsorption-desorption cycles.